2018
DOI: 10.1002/ehf2.12276
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine‐induced cardiomyopathy: a reversible cause of heart failure

Abstract: Chloroquine (CQ) and hydroxychloroquine (HCQ) are anti‐rheumatic medications frequently used in the treatment of connective tissue disorders. We present the case of a 45‐year‐old woman with CQ‐induced cardiomyopathy leading to severe heart failure. Electrocardiographic abnormalities included bifascicular block, while structural disease consisted of severe biventricular and biatrial hypertrophy. Appropriate diagnosis via endomyocardial biopsy led to cessation of CQ and subsequent dramatic improvement in symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 11 publications
0
43
1
1
Order By: Relevance
“…Other studies suggest that older age, duration of medication use, dosage above that recommended by weight, use of CQ instead of HCQ, pre-existing heart disease and renal failure may be risk factors for medication cardiotoxicity. In addition, the risk may be greater in those who use other medications that also lead to prolongation of the QT interval or that increase the serum level of QC [77][78][79]. A study suggested that SLE patients using AM drugs with persistently elevated creatine phosphokinase (CPK) should be monitored periodically and specific biomarkers, such as troponin and brain natriuretic peptide (BNP), may be useful as a screening tool for cardiotoxicity diagnosis by AMs.…”
Section: Cardiotoxicitymentioning
confidence: 99%
“…Other studies suggest that older age, duration of medication use, dosage above that recommended by weight, use of CQ instead of HCQ, pre-existing heart disease and renal failure may be risk factors for medication cardiotoxicity. In addition, the risk may be greater in those who use other medications that also lead to prolongation of the QT interval or that increase the serum level of QC [77][78][79]. A study suggested that SLE patients using AM drugs with persistently elevated creatine phosphokinase (CPK) should be monitored periodically and specific biomarkers, such as troponin and brain natriuretic peptide (BNP), may be useful as a screening tool for cardiotoxicity diagnosis by AMs.…”
Section: Cardiotoxicitymentioning
confidence: 99%
“…Lopinavir/ritonavir can also influence the activity of P2Y 12 inhibitors through CYP3A4 inhibition, which results in decreased serum concentrations of active metabolites of clopidogrel and prasugrel and increased serum concentration of ticagrelor. Cardiac side effects of chloroquine/hydroxychloroquine are rarely reported, but in some cases can be severe and irreversible [107,108]. It is thought to be due to the inhibition of lysosomal enzyme in the myocyte which leads to conduction abnormalities and cardiomyopathy [108].…”
Section: Drug Therapy and Cardiovascular Side Effectsmentioning
confidence: 99%
“…CQ/HCQ can also cause serious and even fatal adverse reactions in heart and retina, epilepsy, extrapyramidal symptom, hypoglycemia, as well as poisoning caused by overdose (H. Liu et al, 2015 ; Yogasundaram, Hung, Paterson, Sergi, & Oudit, 2018 ). The irreversible toxic retinopathy developed after CQ/HCQ treatment is one of the main adverse effects.…”
Section: Cq and Hcq In The Treatment Of Malariamentioning
confidence: 99%